Автоматична компенсація реактивної потужності асинхронного електропривода з тиристорним регулятором напруги - Ковальова, Юлія Вікторівна (Національний технічний університет "Харківський політехнічний інститут", 2018)
Асинхронні електроприводи з тиристорним регулятором напруги працюють в режимі змінного кута керування тиристорами. Мета статті - розробка схеми автоматичної компенсації реактивної потужності для будь-якого кута керування тиристорів. Схема працює наступним чином: визначається кут зсуву першої гармоніки струму статора відносно напруги мережі. Останній перетворюється інтегратором в напругу та подається на вхід чотирирозрядного аналого-цифрового перетворювача (АЦП). На чотирьох виходах АЦП з'являється двійковий код, який відповідає куту зсуву першої гармоніки струму і, отже, відносній величині реактивної потужності. В результаті формується 15 ступеней ємності, що забезпечує автоматичну компенсацію.

The article is devoted to compensation reactive power of AC motors with the thyristor voltage convertor. Reactive power produse the losses of the electrical energy on the transmission lines and substation transformers. The electric diagram of compensation of reactive power contains AC motor, thyristor convertor of voltage, transformer of current and transformer of voltage.The outputs of the first and second rectifiers are connected with the inputs of bloks of impulses of current of stator and voltage of network. The electric diagram contains trigger with two inputs R and S and with a control the falling side of puls. The input S is connected to the output of block of impulses of voltage, and the input R is connected to the output of block of impulses of current. The output of trigger is connected with the input of analog integrator. The output of analog integrator is connected with the input of analog comparator. The output of memory device is connected with the entrance of analog-digital converter. The power outputs of the controlled electron swithes turn on or turn off the first, second, third and fourth condensers for compensation reactive power. The capacities of the second, third and fourth condensers grow in relation to the first with coefficients equal 2,4,8. Such combination of capaciti es of condensers provides the error of compensation reactive power not more than 5%.
Automatic compensation of reactive power ac electric drive with thiristor regulator of voltage
Keywords: асинхронний двигун; AC motor